Disease modeling of a mutation in α‐actinin 2 guides clinical therapy in hypertrophic cardiomyopathy - Maksymilian Prondzynski; Marc D Lemoine; Antonia TL Zech; András Horváth; Vittoria Di Mauro; Jussi T Koivumäki; Nico Kresin; Josefine Busch; Tobias Krause; Elisabeth Krämer; Saskia Schlossarek; Michael Spohn; et al. (EMBO Molecular Medicine)
Abstract Hypertrophic cardiomyopathy (HCM) is a cardiac genetic disease accompanied by structural and contractile alterations. We identified a rare c.740C>T (p.T247M) mutation in ACTN2, encoding α‐actinin 2 in a HCM patient, who presented with left ventricular hypertrophy, outflow tract obstruction, and atrial fibrillation. We generated patient‐derived human‐induced pluripotent stem cells (hiPSCs) and show that hiPSC‐derived cardiomyocytes and engineered heart tissues recapitulated several hallmarks of HCM, such as hypertrophy, myofibrillar disarray, hypercontractility, impaired relaxation, and higher myofilament Ca2+ sensitivity, and also prolonged action potential duration and enhanced L‐type Ca2+ current. The L‐type Ca2+ channel blocker diltiazem reduced force amplitude, relaxation, and action potential duration to a greater extent in HCM than in isogenic control. We translated our findings to patient care and showed that diltiazem application ameliorated the prolonged QTc interval in HCM‐affected son and sister of the index patient. These data provide evidence for this ACTN2 mutation to be disease‐causing in cardiomyocytes, guiding clinical therapy in this HCM family. This study may serve as a proof‐of‐principle for the use of hiPSC for personalized treatment of cardiomyopathies.